Architecture of the Replication Fork Stalled at the 3′ End of Yeast Ribosomal Genes - Gruber, Markus (American Society for Microbiology, 2000)
Every unit of the rRNA gene cluster of Saccharomyces cerevisiae contains a unique site, termed the replication fork barrier (RFB), where progressing replication forks are stalled in a polar manner. In this work, we determined the positions of the nascent strands at the RFB at nucleotide resolution. Within an HpaI-HindIII fragment essential for the RFB, a major and two closely spaced minor arrest sites were found. In the majority of molecules, the stalled lagging strand was completely processed and the discontinuously synthesized nascent lagging strand was extended three bases farther than the continuously synthesized leading strand. A model explaining these findings is presented. Our analysis included for the first time the use of T4 endonuclease VII, an enzyme recognizing branched DNA molecules. This enzyme cleaved predominantly in the newly synthesized homologous arms, thereby specifically releasing the leading arm.